Optimasi Parameter Pasca Cetak SLA 3D Printing Terhadap Karakteristik Kekerasan Material Menggunakan Metode Grey Relational Analysis (GRA) - Abdul Hamid; Rochmad Eko Prasetyaning Utomo; Ganda Surahman (Universitas Islam Malang, 2025)
The demand for durable custom vehicle components requires enhancing the mechanical characteristics of Stereolithography (SLA) materials, which are generally brittle—a gap that must be addressed through post-processing optimization. This study aims to identify the optimal post-processing parameter combinations to maximize the hardness of SLA resin using the Grey Relational Analysis (GRA) method. The experimental design followed a Taguchi L9 orthogonal array, testing four factors Washing Time, Curing Time, Annealing Time, and Annealing Temperature at three levels each, with Shore D hardness as the quality response. The results demonstrated a significant increase in hardness from a baseline of 79.2 Shore D to 82.5 Shore D under optimal conditions. The GRA identified the combination of 15 min Washing Time, 25 min Curing Time, 30 min Annealing Time, and 80°C Annealing Temperature as the optimum setting, resulting in a 16.4% improvement in the Grey Relational Grade (GRG) compared to the experimental mean. ANOVA results confirmed that Washing Time (50.79% contribution, P=0.028) and Annealing Time (41.49% contribution, P=0.034) were the most significant factors (P < 0.05) influencing hardness variation. Conversely, Curing Time was found to be insignificant (P=0.189), suggesting that 15 minutes is sufficient, while residual monomer removal and thermal stress relief during annealing are more critical. Overall, this study concludes that enhancing SLA material hardness depends heavily on thorough cleaning and controlled heat treatment.